Associations between greenness and predicted COVID-19–like illness incidence in the United States and the United Kingdom. Issue 1 (7th February 2023) - Chen, Kelly; Klompmaker, Jochem O.; Roscoe, Charlotte J.; Nguyen, Long H.; Drew, David A.; James, Peter; Laden, Francine; Fecht, Daniela; Wang, Weiyi; Gulliver, John; Wolf, Jonathan; Steves, Claire J.; et al.
Abstract : Background: Green spaces may be protective against COVID-19 incidence. They may provide outdoor, ventilated, settings for physical and social activities and therefore decrease transmission risk. We examined the association between neighborhood greenness and COVID-19–like illness incidence using individual-level data. Methods: The study population includes participants enrolled in the COVID Symptom Study smartphone application in the United Kingdom and the United States (March–November 2020). All participants were encouraged to report their current health condition and suspected risk factors for COVID-19. We used a validated symptom-based classifier that predicts COVID-19–like illness. We estimated the Normalized Difference Vegetation Index (NDVI), for each participant's reported neighborhood of residence for each month, using images from Landsat 8 (30 m 2 ). We used time-varying Cox proportional hazards models stratified by age, country, and calendar month at study entry and adjusted for the individual- and neighborhood-level risk factors. Results: We observed 143, 340 cases of predicted COVID-19–like illness among 2, 794, 029 participants. Neighborhood NDVI was associated with a decreased risk of predicted COVID-19–like illness incidence in the fully adjusted model (hazard ratio = 0.965, 95% confidence interval = 0.960, 0.970, per 0.1 NDVI increase ). Stratified analyses showed protective associations among U.K. participants but not among U.S. participants. Associations were slightly stronger for White individuals, for individuals living in rural neighborhoods, and for individuals living in high-income neighborhoods compared to individuals living in low-income neighborhoods. Conclusions: Higher levels of greenness may reduce the risk of predicted COVID-19–like illness incidence, but these associations were not observed in all populations.